2018
DOI: 10.17294/2330-0698.1495
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Factors and Barriers to Weight Management in Women: Physician Perspectives

Abstract: Journal of Patient-Centered Research and Reviews ( JPCRR) is a peerreviewed scientific journal whose mission is to communicate clinical and bench research findings, with the goal of improving the quality of human health, the care of the individual patient, and the care of populations. Recommended CitationWalker RE, Kusch J, Fink JT, Nelson DA, Morris G 3rd, Skalla J, Cisler RA. Facilitating factors and barriers to weight management in women: physician perspectives. J Patient Cent Res Rev. 2018;5:18-27. doi: 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Lifestyle modifications potentially have substantial benefits to overall and RMD-specific health and should be a recurrent and frequent theme in discussions between people with RMDs and health professionals. Furthermore, given the complexity of RMD conditions (eg, early vs established disease, disease flares) and the potential interactions between lifestyle modifications, current health condition and medical treatment, people with RMDs may need guidance and support from health professionals to implement a combination of healthy lifestyle changes 32–34. This guidance and support should stem from a comprehensive management plan known to all health professionals directly involved in the disease management of people with RMDs.…”
Section: Resultsmentioning
confidence: 99%
“…Lifestyle modifications potentially have substantial benefits to overall and RMD-specific health and should be a recurrent and frequent theme in discussions between people with RMDs and health professionals. Furthermore, given the complexity of RMD conditions (eg, early vs established disease, disease flares) and the potential interactions between lifestyle modifications, current health condition and medical treatment, people with RMDs may need guidance and support from health professionals to implement a combination of healthy lifestyle changes 32–34. This guidance and support should stem from a comprehensive management plan known to all health professionals directly involved in the disease management of people with RMDs.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, from the physician's perspective, studies have referenced physicians feeling they had insufficient training to have meaningful and impactful conversations regarding weight management with patients. 20 Additionally, physicians often perceive patients as lacking motivation to address their weight rather than considering potential social and ecological barriers to proper weight management. 20 Such discrepancies present in perceptions between patients and physicians builds a picture of present deficits in patient-provider communication, and potentially highlights areas for targeted improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al describe physician perspectives on barriers to weight management for women. 13 Out of focus groups conducted with internal and family medicine physicians, a few critical themes emerged --involvement of the primary care setting, communication between patient and provider, and acknowledgment of patient motivation to manage weight. The researchers concluded that a multidisciplinary approach will be crucial to making progress on this often sensitive but serious health concern.…”
Section: From the Editormentioning
confidence: 99%